U‐Pb dating of zircons from an impact melt of the Nördlinger Ries crater - Schwarz, Winfried H.; Hanel, Michael; Trieloff, Mario (Meteoritics & planetary science, 2020)
In situ U‐Pb measurements on zircons of the Ries impact crater are presented for three samples from the quarry at Polsingen. The U‐Pb data of most zircons plot along a discordia line, leading to an upper intercept of Carboniferous age (331 ± 32 Ma [2σ]).